Comparative appraisal of multilateral and bilateral approaches to financing private sector development in developing countries - Peter Gibbon; Lau Schulpen (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2002)
This paper identifies the rationale behind the emergence of private sector development (PSD) as a special area of development assistance. It describes PSD policies' main elements and instruments and provides an overview of the differences and similarities between the PSD activities of bilateral and multilateral development agencies. In so doing it asks whether agencies' apparent reliance on the same analytical source extends to the use of the same type of instruments. It also examines how far the latter are consistent with donors' broader development objectives and development assistance norms. It then asks what do the findings reached in this regard imply for aid coherence, coordination and inter-donor competition. Next, the paper provides an overview of discussions around the effectiveness of the numerous PSD instruments. It concludes with a provisional summing-up of the extent to which bilaterals and multilaterals differ, and of why this might be the case.
Keywords: F34; F35; O14; O19; 330; private sector development; development cooperation; bilateral aid; multilateral aid; Privatwirtschaft; Entwicklungshilfe; Entwicklungskooperation; Entwicklungsländer